Evaluasi Hasil Belajar Menggunakan Penilaian Autentik Pada Mata Pelajaran Kelistrikan Sistem Refrigerasi - Rusdiana, Herman (2014)
Penelitianinibertujuanuntuk mengukur tingkat pencapaian kompetensi peserta didik pada ranah afektif, kognitif, dan psikomotordenganmenerapkanpenilaiankurikulum 2013 yaitupenilaianautentik.Penelitianinimenggunakanmetodeeksperimenjenispre-experimental design.Model eksperimen yang digunakanadalahOne-Shot Case Study.Padadesaininitidakterdapatpre testsebelumdiberiperlakuan, karenahasil yang diharapkanbukanuntukmembandingkanataumeningkatakanhasilbelajar, akantetapihanyauntukmengevaluasisejauhmanaketercapaiankompetensi yang dimilikiolehpesertadidikdenganmengacukepadaKriteriaKetuntasan Minimum (KKM). Hasilpenelitianpadaranahafektif, 78,12% pesertadidikmendapatkannilai di atas KKM, pencapaiankompetensipadaranahinipesertadidiktermasukpadakategoricukup. Padaranahkognitif, 93,75% pesertadidikmendapatkannilai di atas KKM, pencapaiankompetensipadaranahinipesertadidiktermasukpadakategoricukup.Sementarapadaranahpsikomotor 84,38% pesertadidikmendapatkannilai di atas KKM, pencapaiankompetensipadaranahini, pesertadidiktermasukpadakategoriterampil. Pesertadidik yang mendapatkannilai di bawah KKM, akanmenjadibahanevaluasibagi guru untukmemperbaikikualitaspembelajaran. Berdasarkanhasilpenelitiantersebut, dapatdisimpulkanbahwapenilaianautentikdapatmengukurtingkatpencapaiankompetensipesertadidikpadaranahafektif, kognitifdanpsikomotor Kata kunci: evaluasi, hasilbelajar, penilaianautentik, kurikulum 2013. This study was aimed to measure the level of students' competence achievement in the affective, cognitive, and psychomotor domains by applying the assessment of curriculum 2013 called authentic assessment. this study used pre-experimental design. one-shot case study was used as the experimental model. in this design, there was no pretest conducted before the treatment because the expected result was not to compare or improve the learning outcomes, but only to evaluate the extent of competence achievement which was owned of the students by referring to the the minimum completeness criteria (KKM). The resultsof researchonthe affective domain,78,12% students got scores above the minimum score, achievement ofcompetenceinthisdomain, studentsincluded inthe category offairly. in the cognitive domain, 93,75% students got scores above the minimum score, achievement ofcompetenceinthisdomain, studentsincluded inthe category offairly. while in the psychomotor domain, 84,38% students got scores above the minimum score, achievement ofcompetenceinthisdomain, studentsincluded inthe category offairly. students who got scores under the minimum score would be the evaluation materials for teachers to improve learning quality. Based on these results,it can be concludedthat authentic assessmentcan measurethe level ofachievement ofcompetence of studentsonthe affective, cognitiveandpsychomotor. Keywords: evaluation, learning outcomes, authentic assessment, curriculum 2013.